1993
DOI: 10.3354/dao015129
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profiling as an epidemiological marker within Aeromonas salmonicida

Abstract: A collect~on of 124 isolates of Aeromonas salmonicida ssp. salmonicida from Denmark, Norway, Scotland, and North America was plasmid profiled. All stralns contained at least 1 large plasmid in the range of 60 to 150 kb, and all stralns possessed 2 low-molecular-weight plasmids of 5.2 a n d 5.4 k b Two a d d~t~o n a l low-molecular-weight plasmlds of 5.6 and 6.4 kb were frequently encountered. A total of 23 different plasrnids were demonstrated, 12 of them being found In more than one country. Forty d~fferent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…Methods applied to typical Aeromonas salmonicida such as DNA:DNA reassociation (Belland & Trust 1988), plasmid profiling (Nielsen et al 1993, Sørum et al 2000, ribotyping (Nielsen et al 1994), DNA probes (Gustafson et al 1992), restriction endonuclease analysis (McCormick et al 1990), random amplified polymorphic DNA analysis (RAPD) (Hänninen et al 1995, Miyata et al 1995 and restriction fragment length polymorphism analysis by pulsed field gel-electrophoresis (PFGE) (Livesley et al 1999), all demonstrate the typical isolates to be extremely homogeneous. Similar studies on atypical strains using RAPD analysis (Kwon et al 1997, O'hIci et al 2000, ribotyping (Hänninen & Hirvelä-Koski 1997), PCR-typing (Høie et al 1999), plasmid profiling (Sørum et al 2000) and restriction fragment analysis by PFGE (Umelo & Trust 1998, O'hIci et al 2000, have shown them to be more genetically diverse compared to the typical strains.…”
Section: Introductionmentioning
confidence: 99%
“…Methods applied to typical Aeromonas salmonicida such as DNA:DNA reassociation (Belland & Trust 1988), plasmid profiling (Nielsen et al 1993, Sørum et al 2000, ribotyping (Nielsen et al 1994), DNA probes (Gustafson et al 1992), restriction endonuclease analysis (McCormick et al 1990), random amplified polymorphic DNA analysis (RAPD) (Hänninen et al 1995, Miyata et al 1995 and restriction fragment length polymorphism analysis by pulsed field gel-electrophoresis (PFGE) (Livesley et al 1999), all demonstrate the typical isolates to be extremely homogeneous. Similar studies on atypical strains using RAPD analysis (Kwon et al 1997, O'hIci et al 2000, ribotyping (Hänninen & Hirvelä-Koski 1997), PCR-typing (Høie et al 1999), plasmid profiling (Sørum et al 2000) and restriction fragment analysis by PFGE (Umelo & Trust 1998, O'hIci et al 2000, have shown them to be more genetically diverse compared to the typical strains.…”
Section: Introductionmentioning
confidence: 99%
“…DNA:DNA reassociation analysis (Belland & Trust 1988), plasmid profiling (Nielsen et al 1993), ribotyping (Nielsen et al 1994), DNA probes (Gustafson et al 1992, Hiney et al 1992. restriction endonuclease analysis (McCormick et al 1990), random amplified polymorphic DNA analysis (Hanninen et al 1995, Miyata et al 1995, and pulsed-field gel electrophoresis (PFGE) (Umelo & Trust 1998) have concentrated on A. salmonicida subsp.…”
Section: Introductionmentioning
confidence: 99%
“…; Byers et al . ), including 25% of 57 examined Danish strains (Nielsen, Olsen & Larsen ). Some authors explain the missing plasmid by stressful culturing conditions above 22–25°C, which was shown to activate an pAsal1 insertion sequence element IS AS11 that leads to the loss of the plasmid (Daher et al .…”
Section: Discussionmentioning
confidence: 99%